Pengujian Perundang – Undangan : Legislative Review Executuve Review dan Judicial Review - Wilma Silalahi; Yunita Estu Lestari (PT PUSTAKA CENDEKIA GROUP, 2025)
In a constitutional state, every legal product must comply with the Constitution to ensure legal certainty, democracy, and the protection of citizens’ constitutional rights. However, the legislative process in Indonesia often faces disharmony, regulatory overlaps, and laws that fail to meet societal needs. This study aims to analyze the mechanisms of legislative review, executive review, and judicial review within the Indonesian legal system and to assess the challenges and solutions in their implementation. The research employs a normative legal method with a conceptual approach, examining constitutional law theories, the principle of checks and balances, and existing statutory regulations, supported by primary and secondary legal sources. The findings reveal that: (1) the three forms of review have distinct meanings, legal foundations, and functions, yet complement each other in safeguarding constitutionalism; (2) each branch of power holds specific authority—legislative review is exercised by the DPR and the President, executive review by ministries and the President, and judicial review by the Constitutional Court and the Supreme Court; (3) significant challenges remain, such as political dominance in legislative review, regulatory disharmony in executive review, and limited access as well as inconsistent rulings in judicial review. The study concludes that although Indonesia has a complete system of legal review, its effectiveness depends on the quality of legislation, institutional coordination, and compliance with judicial decisions. Therefore, this research recommends three key measures: strengthening public legal literacy, enhancing the technical capacity of state institutions, and implementing integrated cross-sector reforms to reinforce transparency, participation, and legal compliance.